Answer:
x =
y =
![-(8)/(5),1](https://img.qammunity.org/2022/formulas/mathematics/high-school/1sjh5ek1i15vxu7oq9l7028hgcc6ypjt5l.png)
Explanation:
3xy - y² = 8 -------(1)
x - 2y = 1 ------(2)
From equation (2),
x = 2y + 1
By substituting the value of x in equation (1),
3y(2y + 1) - y² = 8
6y² + 3y - y² = 8
5y² + 3y - 8 = 0
5y² + 8y - 5y - 8 = 0
y(5y + 8) - 1(5y + 8) = 0
(y - 1)(5y + 8) = 0
y =
![-(8)/(5),1](https://img.qammunity.org/2022/formulas/mathematics/high-school/1sjh5ek1i15vxu7oq9l7028hgcc6ypjt5l.png)
From equation (2),
x = 2y + 1
For y =
,
x =
x =
![-(11)/(5)](https://img.qammunity.org/2022/formulas/mathematics/high-school/ltqmg19eaxj3rzwz8g76klxvogucaa9c65.png)
For y = 1,
x = 2(1) + 1
x = 3
Therefore, x =
y =
![-(8)/(5),1](https://img.qammunity.org/2022/formulas/mathematics/high-school/1sjh5ek1i15vxu7oq9l7028hgcc6ypjt5l.png)